Posner, Economics and the Law: from Law and Economics to an Economic Analysis of Law - Alain Marciano
The purpose of this article is to discuss Posner's economic analysis of law and to analyse the differences between his economic analysis of law and law and economics. We propose and demonstrate a twofold original argument. First, we show that Posner does not only propose an economic analysis of the working of the legal system but also that his approach has changed in the early 1970s, shifting from a law and economics perspective in which the focus is put on the working of the economic system to an economic analysis of law in which the emphasis is put on the functioning of the legal system. He appears then no longer influenced by Aaron Director and Ronald Coase but rather by Gary Becker. Therefore, and this is the second part of our demonstration, we show that the evolution in Posner's works essentially derives from the influence of Becker and the adoption by the former of the methodological views of the latter. More precisely, we claim that Posner no longer retains a -- restrictive -- definition of economics by subject matter but that he aligns himself on Becker and his broader definition of economics placing nonmarket decisions and method at the core of the discipline. In other words, we argue that Posner is the first who transposes Becker’s definition of economics in law and economics and that this is precisely what makes Posner's economic analysis of law possible and specific, and also of particular importance.